Effect of Chlorogenic Acids on Cognitive Function in Mild Cognitive Impairment: A Randomized Controlled Crossover Trial - Ochiai, Ryuji (J Alzheimers Dis, 2019)
BACKGROUND: Mild cognitive impairment (MCI) is a global-scale issue, due in large part to the rapidly growing elderly population. The main polyphenol contained in coffee beans, chlorogenic acid (CGA), improves attention in healthy individuals. The utility of CGAs for treating MCI, however, has not been evaluated. OBJECTIVE: To determine the effects of continuous CGA intake on cognitive function, especially attention, in patients diagnosed with MCI. METHODS: The study was a randomized controlled crossover trial including 34 patients with MCI. Participants were randomly divided into two groups: Those who first ingested a placebo beverage and those who first ingested an active beverage containing CGAs (553.6 mg/bottle) twice daily for 12 weeks. After a 4-week washout period, the subjects ingested the other beverage (i.e., placebo or active beverage) in the same manner. Endpoint measures included scores on the Japanese version of the Mini-Mental State Examination (MMSE), the Japanese version of the Alzheimer’s Disease Assessment Scale-cognitive component (ADAS-cog) testing overall cognitive function, and the Japanese version of the Trail Making Test (TMT-A, TMT-B) testing attention, along with the results of blood tests to evaluate safety. RESULTS: In the TMT-B test, participants had a significantly reduced number of errors while ingesting the CGA beverage as compared with the placebo beverage (p < 0.05), although there was no difference in test completion time. Scores in the MMSE, ADAS-cog, and TMT-A did not differ significantly between conditions. CONCLUSION: Continuous intake of CGAs appears to improve attention and executive function among cognitive functions in MCI.